Balance between Privacy Protecting and Selling User Data of Wearable Devices - Kuang-Chiu Huang; Jung-Fang Hsu (International Telecommunications Society (ITS), 2017)
Smart bracelets are capable of identifying individual data, which can synchronize the step count, mileage, calorie consumption, heart rate, sleeping data and even the pictures users uploaded with the APP. This feature is so convenient on one hand but makes us lose control of our privacy on the other hand. With poor privacy protection mechanism embedded in these wearable devices that hackers can easily invade and steal user data. In addition, most smart bracelet companies have not made a clear declaration of which third parties are able to get users' data, nor how long will the user's physical and health-related information be stored. These companies understand well that large amount of the user's movement and physiological monitoring data are valuable, because each user's information can be a unique sample. As soon as the smart bracelet companies collect extensive and diverse samples, they can figure out a variety of specific and practical applications through excavate data. Therefore, the research questions of this study are 1. how do smart bracelet companies strike a balance between protecting consumer privacy and selling user data to get more business opportunities? 2. In order to achieve this balance, what kind of strategy should smart bracelet companies adopt? This study addresses what measures smart bracelet companies take as well as what attitude they hold through literature review and the comparison of Fitbit, Xiaomi and Garmin's privacy policies. Meanwhile we adopt PEST analysis model and Porter's diamond model to engage external analysis of three main vendors in order to have a further understanding of the environment in which the industry is poised. At last, we apply the stakeholder analysis to determine what strategies the companies should take in correspondence after identifying the direct and indirect stakeholders of the smart bracelet companies. This research outcome indicates that beneficial tangible service is the main factor affecting consumers whether to share their data with wearable vendors, but vendors have to be aware of the impacts of privacy issues by selling user data. It is possible that consumers resist buying the wearable products if they find their privacy is disturbed. Furthermore, this study is valuable not only to wearable device vendors to strike balance between privacy and profits but also policy makers to figure out the necessity to get involve in personal data protection over wearable device market.
Keywords: 330; wearable devices; smart bracelet; user privacy; PEST analysis; diamond model; stakeholder analysis